Women in patriarchy : cross-cultural readings - Jain, Jasbir (Jaipur : Rawat Publications, 2005)
Contributed literary pieces by women authors from the India and developed nations.
Literature.
Keywords: INDIC LITERATURE (ENGLISH) -- 20th CENTURY; ENGLISH LITERATURE -- 20th CENTURY; WOMEN -- LITERARY COLLECTIONS; PATRIARCHY -- LITERARY COLLECTIONS